Enhancing social-emotional skills in early childhood: intervention study on the effectiveness of social and emotional learning - Rikuya Hosokawa; Yuki Matsumoto; Chizuko Nishida; Keiko Funato; Aki Mitani (BMC Psychology)
Abstract Background Social and emotional learning (SEL) is crucial for developing skills such as emotional regulation, cooperation, and goal achievement. Deficits in these skills are linked to later academic and behavioral problems. While SEL interventions have been widely implemented internationally, few have been tested in early childhood settings in Japan, and their effectiveness remains unclear. In 2022, the Fun FRIENDS social and emotional learning program was introduced in class units for 4–5-year-olds attending kindergartens and children’s schools in Wakayama Prefecture, Japan. Thus, this study examined the effectiveness of the Fun FRIENDS program in children aged 4–5 years in Japan. Methods Fun FRIENDS is based on a cognitive-behavioral approach designed to teach participants how to cope with anxiety and stress, and to develop resilience and confidence. The program consists of 10 weekly sessions of approximately 1 h each. The intervention group comprised 115 children from two facilities, while the control group comprised 93 children from three facilities. Intervention effectiveness was evaluated through changes in externalizing (e.g., aggression, oppositional behavior) and internalizing behaviors (e.g., anxiety, depression), measured using the Strengths and Difficulties Questionnaire. Finally, data from 94 participants in the intervention group and 66 participants in the control group were analyzed. Results In the intervention group, externalizing behaviors showed a significant reduction both before and after the intervention and internalizing behaviors also decreased significantly. Conversely, the control group did not exhibit any significant changes in either externalizing or internalizing behaviors before or after the intervention. The effect size for externalizing behaviors in the target group was 0.744, while the effect size for internalizing behaviors was 0.653. Conclusions Social and emotional learning programs in classrooms may effectively control problem behaviors in early childhood and prevent school maladjustment. A whole-class approach can reach more children, maximizing the preventive effects. The program can improve academic performance and social adaptation, contributing to the long-term development of psychological health and social skills. Nevertheless, further longitudinal research is required to assess the program’s long-term effects. In summary, strengthening the focus on social-emotional learning in early childhood education policy is key to realizing long-term benefits for child development.